Oil and natural gas development influence nest‐site selection and nest survival of upland‐nesting waterfowl and shorebirds - Sarah M. Ludlow; Stephen K. Davis (Wildlife Society Bulletin)
ABSTRACT Native grasslands provide important breeding habitat for many upland‐nesting waterfowl and shorebirds. However, recent increases in oil and gas development in native grassland may alter the quantity and quality of this globally threatened habitat. Oil and natural gas development involves construction of roads, trails, and wells; often facilitating invasion by exotic vegetation. Our objectives were to determine 1) whether nest placement by upland‐nesting waterfowl and shorebirds varied with proximity to oil and gas infrastructure; and 2) the extent to which nest survival was influenced by proximity to wells, roads, and trails, as well as percent cover of the exotic crested wheatgrass in southeastern Alberta, Canada, 2010–2011. Mallard (Anas platyrhynchos) and blue‐winged teal (Spatula discors) nests were located within 100 m of wells more than expected by chance, and northern shoveler (Spatula clypeata) and northern pintail (Anas acuta) tended to nest more frequently within 200 m of wells. In contrast, more shorebird nests were located farther from wells than expected. Mallards and blue‐winged teal were also more likely to place their nests near roads. Shorebirds tended to place their nests either close to roads or far from these structures more often than expected by chance. The proportion of mallard nests located in close proximity to trails was greater than expected, but fewer blue‐winged teal nests were located near trails than expected by chance. The top‐ranked models explaining variation in daily nest survival rates of northern shoveler, mallard, and shorebirds included distance to infrastructure variables, although these relationships were weak. Northern shovelers appear to benefit from placing nests closer to trails; daily nest survival rate increased with proximity to trails. However, trails may act as an ecological sink for shorebirds; they were more likely to place nests near trails but daily survival rates were lower near trails. © 2018 The Wildlife Society.